Isolation and chemical investigation of bixin from Bixa orellana Linne (Family Bixaceae) - Cruz, Ma. Elizabeth F.; Concepcion. Adoracion B.; Cruz, Ileana R. (Manila Department of Pharmaceutical Chemistry, College of Pharmacy, University of the Philippines, 1985)
Annatto extract contained in the pericarp of the fruit Bixa orellana (Fam. Bixaceae) is extracted by Soxhlet Extraction using boiling chloroform as the solvent.
The major constituent extracted is bixin with a percentage yield of 4.74%. Its melting point is 180-182℃ using the Meltemp.
Separation of the yellow and orange pigments is done by performing thin layer chromatography using butyl alcohol-ethyl alcohol-water; chloroform-methanol; and benzene-ethyl acetate, and by performing column chromatography using petroleum ether-methanol as solvent system.
​Thesis (Bachelor of Science in Industrial Pharmacy)--University of the Philippines, October 1985.
Keywords: Annatto tree; Achuete; Atseuete